The Effect of Alkali Concentration and Sodium Silicate Modulus on the Properties of Alkali-Activated Slag Concrete - Taghvayi, Hamed; Behfarnia, Kiachehr; Khalili, Mohammadbagher (Journal of Advanced Concrete Technology, 2018)
In this study, the effect of alkali concentration and sodium silicate modulus of the activator solution on workability, compressive strength, and drying shrinkage of alkali-activated slag (AAS) concrete was investigated experimentally. Twenty mixes were prepared with the ground granulated blast furnace slag (GGBFS) activated with the various alkali concentrations and sodium silicate modulus. The compressive strength at the ages of 7, 28 and 90 days was measured and the drying shrinkage of the concrete samples up to 400 days were measured. Based on the results, in most mixes, by increasing the sodium silicate modulus and the concentration of the alkali solution, the slump, compressive strength, and the rate of the drying shrinkage of the samples were increased, but the setting time was reduced. These results were contrary to those specimens cast with high alkalinity. The effect of the sodium silicate modulus was much higher than the concentration of the alkali solution on the drying shrinkage of the samples. In order to evaluate the effect of the alkali concentration and the silicate modulus on the microstructure and the reaction product of the AAS paste, x-ray diffraction (XRD) analysis and scanning electron microscopy (SEM) images were examined.